COVID-19 and Maritime Transport: Impact and Responses - United Nations Conference on Trade; Development (United Nations, 2021)
The report describes and analyses the impact of COVID-19 (coronavirus) on the maritime supply chain. It also identifies response measures adopted and sets out a list of lessons learned and good practices in resilience building and disruption management.